Initiation of the West Antarctic Ice Sheet and estimates of total Antarctic ice volume in the earliest Oligocene. Issue 16 (27th August 2013) - Wilson, Douglas S.; Pollard, David; DeConto, Robert M.; Jamieson, Stewart S.R.; Luyendyk, Bruce P.
Abstract [1] Reconstructions of Antarctic paleotopography for the late Eocene suggest that glacial erosion and thermal subsidence have lowered West Antarctic elevations considerably since then, with Antarctic land area having decreased ~20%. A new climate‐ice sheet model based on these reconstructions shows that the West Antarctic Ice Sheet first formed at the Eocene‐Oligocene transition (33.8–33.5 Ma, E‐O) in concert with the continental‐scale expansion of the East Antarctica Ice Sheet and that the total volume of East and West Antarctic ice (33.4–35.9 × 106 km3) was >1.4 times greater than previously assumed. This larger modeled ice volume is consistent with a modest cooling of 1–2°C in the deep ocean during the E‐O transition, lower than other estimates of ~3°C cooling, and suggests the possibility of substantial ice in the Antarctic interior before the Eocene‐Oligocene boundary.